(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Social enterprise is no exception as all organizations must generate enough revenue to survive. However, social enterprise has different definitions and characteristics to business enterprise that adjustments to the Canvas are necessary to fully capture the business model of a social enterprise. The paper contends that social enterprise sustainability is grounded in understanding the impact of contextual, organizational and individual spheres that correspond to three strategic ex-ante enablers stakeholder orientation, relationship-oriented Organisation, and entrepreneurial behaviour all of which have had valuable contributions towards the upkeep of the enterprise. The study demonstrates that sustainability of social enterprises in a constrained environment is a function of a continuous entrepreneurial activity and the effective use of social and business models.